Management of mild cognitive impairment (MCI): The need for national and international guidelines. (13th September 2020) - Kasper, Siegfried; Bancher, Christian; Eckert, Anne; Förstl, Hans; Frölich, Lutz; Hort, Jakub; Korczyn, Amos D; Kressig, Reto W.; Levin, Oleg; Palomo, María Sagrario Manzano
Abstract: Objectives: To review available evidence of pharmacological and non-pharmacological treatment for MCI and analyse information and limitations in national and international guidelines. Methods: Experts from several European countries conducted a qualitative review of the literature on MCI and treatments for MCI, as well as respective chapters in national and international guidelines on dementia/MCI. Psychotherapeutic/psychosocial treatments were excluded from the review. Results: Consensus diagnostic criteria for MCI are available, making early recognition and accurate classification of MCI subtypes possible. MCI can be identified in a primary care setting. Further corroboration and differential diagnosis should be done at specialist level. Mixed pathologies are the rule in MCI, thus a multi-target treatment approach is a rational strategy. Promising evidence has been generated for multi-domain interventions. Limited evidence is available for different pharmacological classes that have been investigated in MCI clinical trials (e.g. acetylcholinesterase inhibitors). EGb 761 ® improved symptoms in some clinical trials; it is the only pharmacological treatment recommended in existing guidelines for the symptomatic treatment of MCI. Conclusions: MCI is recognised as an important treatment target and some recent national guidelines have considered symptomatic treatment recommendations for MCI. However, more needs to be done, especially at an international level.